Intravoxel Incoherent Motion Analysis of Abdominal Organs: Application of Simultaneous Multislice Acquisition. Issue 3 (March 2018) - Phi Van, Valerie Doan; Becker, Anton S.; Ciritsis, Alexander; Reiner, Caecilia S.; Boss, Andreas
Abstract : Purpose: The aim of this study was to systematically evaluate the accuracy of quantitative intravoxel incoherent motion (IVIM) analysis of the upper abdomen applying simultaneous multislice (SMS) diffusion-weighted imaging (DWI) to reduce acquisition time. Materials and Methods: Diffusion-weighted imaging of parenchymal abdominal organs was performed in 8 healthy volunteers at 3 T using a standard DWI sequence (acceleration factor 1 [AF1]) and an SMS-accelerated echo planar imaging sequence with acceleration factors 2 and 3 (AF2/AF3). Intravoxel incoherent motion analysis was performed with a multistep algorithm for true diffusion coefficient ( D t ), pseudodiffusion coefficient ( D *), and fraction of perfusion ( F p ) measured for the liver, kidney cortex and medulla, pancreas, spleen, and erector spinae muscle. Qualitative and quantitative parameters were compared using a repeated measurement 1-way analysis of variance test and the Bonferroni post hoc method. Results: Simultaneous multislice DWI provided diagnostic image quality in all volunteers with a reduction of scan time of 50% for AF2 (67% for AF3) compared with the standard sequence. Decent IVIM analysis for D t, D *, and F p can be calculated on the images of both the SMS sequences AF2 and AF3 with typical organ characteristics of IVIM; however, systematical deviations from AF1 were observed: D t values increased and F p decreased significantly with higher acceleration factor for liver, kidney, pancreas, and muscle ( P < 0.05). Fitting curves of higher acceleration factors tend to be more monoexponentially shaped. Conclusions: Simultaneous multislice acceleration provides considerable scan time reduction for upper abdomen DWI with equivalent quality of IVIM analysis compared with the standard nonaccelerated technique. Systematic discrepancies of the true D t, D *, and F p for SMS acquisitions need to be considered when comparing to standard DWI sequences.